A Short Review on the Bioactive Constituents from Six Terminalia Species - Hussain, Mohammad Musarraf (Bangladesh Pharmaceutical Journal, 2021)
Terminalia as a genus has received a great attraction to evaluate and examine the pharmacological potential having their medicinal properties. Different species under Terminalia genus have been used as herbal medicine with various formulations in the treatment of abdominal pain, cancer, cough, conjunctivitis, diarrea, heart problem, leproscopy, urinary tract infection, and sexual related diseases. These properties have been reported to express abundant biological characteristics for example antioxidant, antiparasitic, antibacterial, antifungal, antiviral, and anti-inflammatory. This review has constructed to solicitude the phytochemicals from the genus Terminalia. A total six species belongs to this genus such as Terminalia chebula, T. citrina, T. phanerophlebia, T. belerica, T. catappa, and T. arjuna have been studied and fifty-six phytochemicals with their chemical structures have been reported in this review. Terminalia chebula consists of a higher number of phytochemicals as compared to the other species. Bangladesh Pharmaceutical Journal 24(1): 76-82, 2021